Tingkat kepuasan pasien terhadap mutu pelayanan kesehatan gigi dan mulut di rsud dr. Rubini mempawah - Rubini; Lia Hapsari Andayani (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Patient satisfaction is the goal of providing health services and is a sign of the good quality of services provided. The Regional General Hospital (RSUD) dr.Rubini Mempawah is a referral center for all level one health facilities in Mempawah Regency. Purpose: to describe the level of patient satisfaction with the quality of dental and oral health services at RSUD dr.Rubini Mempawah. Methods: This descriptive observational study with a cross-sectional design was conducted from August to September 2021. A total of 200 respondents were taken using a consecutive sampling technique. The instrument in the form of a questionnaire consists of five dimensions of Service Quality, namely reliability, responsiveness, assurance, empathy, and tangible. Results: The results showed that the majority of respondents were satisfied with the dimensions of responsiveness (51%), assurance (47%), empathy (48%), and tangible (50%). Most of the respondents only felt quite satisfied with the reliability dimension (49%). Conclusion: This study shows the need to improve the quality of dental and oral health services in RSUD dr. Rubini Mempawah especially on the dimension of reliability.